THE JAVANESE QUEST OF ISLAMIC SPIRITUALITY IN SULUK WUJIL: A SEMIOTIC READING - Ahwan Fanani (Analisa: Journal of Social Science and Religion, 2018)
Javanese Islamic Literature was connected to Islamic mysticism and written in poem to express delicate and sophisticated doctrines. Poem is deemed to be able to go beyond literal meaning for it expresses notion through figurative languages. Suluk Wujil is a good example of such early Javanese Islamic literary work that features spiritual quest and teaching. Suluk Wujil tells about Wujil, a convert who wanted to reach the essence of the ultimate Truth. Wujil is symbolic figure carrying an important sufistic teaching as well as the revealing socio-religious discourse in the early development of Islam in Java. This article is aimed to reveal the content of Suluk Wujil using three steps of semiotic reading, i,e, narrative schema, primary sign discovery and syntagmatic as well as paradigmatic analysis. The paper shows, firstly, that narrative scheme of Suluk Wujils is proceeded by a complaint of Wujil who failed to get into The Ultimate Truth after ten years of spiritual learning in Bonang. Ratu Wahdat or Sunan Bonang taught him the way to get spiritual enlightenment along with endorsing spiritual enlightenment of Seh Malaya (Sunan Kalijaga). Secondly, the primary sign of the Wujil Suluk is the phrase "Arriving in Mecca", in the last part of the text. The phrase affirms the spiritual characteristic of Suluk Wujil, with concern to a spiritual journey to very truth of Islamic spirituality. Thirdly, the paradigmatic analysis shows that there are various signs parallel and oppositional in the same time. The combination of signs forms a synthesis which leads to a deeper understanding of the significance of the signs. The syntagmatic analysis leads to an understanding of oppositional, but complementary signs.